A New Interpretation of the Iron Age Negev Highlands Sites - Ben-Yosef, Erez (Antiguo Oriente, 2026)
During the early Iron Age, hundreds of sites emerged across the Negev Highlands of southern Israel. These sites have traditionally been interpreted as part of a settled society, such as the United Monarchy, the Edomite kingdom, or a local “desert polity” undergoing sedentarization. In light of recently published data, I argue that they instead represent function-specific installations along the northwestern frontier of a nomadic tribal polity that controlled an extensive region, including the Arabah Valley and probably also the southern Transjordanian Plateau. While this polity was largely archaeologically invisible in terms of its population’s dwellings, its engagement in copper production and exchange generated pronounced archaeological remains, including the mining centers in the Arabah and the Negev Highlands sites. Rather than reflecting permanent settlement—whether of external or local populations—these remains primarily document specific economic, logistical, and territorial dimensions of nomadic political organization, with the Negev Highlands sites functioning chiefly as trading hubs, protection and coordination nodes, and frontier markers. Their prominence in an otherwise archaeologically empty landscape should not be confused with evidence for “settlements” or sedentary occupation; likewise, the end of their use does not indicate societal collapse, but rather the cessation of copper production and its associated exchange systems. I further argue that this interpretive framework is equally applicable to the Early Bronze Age sites in the region. Despite differences in site plan and chronology, these sites share comparable characteristics, including close ties to Arabah copper production and the demonstrable absence of agriculture, and likewise reflect neither the arrival of new populations nor a sedentarization process, but instead the episodic archaeological visibility of a society that remained essentially nomadic throughout.